2011
DOI: 10.4028/www.scientific.net/amr.343-344.160
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cu Dopant on the Microstructure and Non-Ohmic Electrical Properties of ZnO Varistors

Abstract: The doping effects of Cu on the microstructure and non-ohmic electrical properties of ZnO varistors were studied. Addition of Cu2O can enhance the ZnO grain growth during sintering. The SEM and EDS results revealed that the added Cu mainly distributed in the grain boundary and spinel phases of ZnO varistors. The Cu2O addition increased the both of grain and grain boundary resistances. However it decreased the non-ohmic electrical characteristics of ZnO varistors, which is a good agreement with similar findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In contrast, Zhou et al [8] reported the Cu-doped ZnO samples shows linear I-V characteristics. Fan et al [11] reported that the Cu 2 O addition could deteriorate the electrical properties of ZnO varistor. However, the effects of monovalent Cu on the electrical characteristics of ZnO based varistors need to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Zhou et al [8] reported the Cu-doped ZnO samples shows linear I-V characteristics. Fan et al [11] reported that the Cu 2 O addition could deteriorate the electrical properties of ZnO varistor. However, the effects of monovalent Cu on the electrical characteristics of ZnO based varistors need to be further investigated.…”
Section: Introductionmentioning
confidence: 99%